Pete the cat - Super Pete - Dean, Kimberly; Dean, James 1957-
Donning a cape and sneakers, Pete the Cat assumes his groovy alter ego, Super Pete, and takes down bad guys using crimefighting gadgets from his secret underground lair
Keywords: Pete / the Cat (Fictitious character) / Juvenile fiction; Cats / Juvenile fiction; Superheroes / Juvenile fiction; Pete / the Cat (Fictitious character) / Fiction; Cats / Fiction; Superheroes / Fiction; Humorous stories; JUVENILE FICTION / Readers / Beginner; Pete / the Cat (Fictitious character); Cats; Superheroes; Pete / the Cat (Fictional character) / Fiction; Robbery / Fiction; Animals / Fiction; Readers (Elementary); Humorous fiction; Fiction; Juvenile works; Readers (Publications); Bilderbuch